Suggested consensus for the diagnosis of gestational diabetes. (January 2014) - Donaldson, Samantha; McIntyre, David
SUMMARY  Recent proposals for the revision of diagnostic criteria for gestational diabetes mellitus (GDM) have engendered worldwide debate. Within and between countries there is disagreement between obstetric, medical and endocrine groups regarding the diagnosis and management of GDM. There have been many articles written recently on this topic in an attempt to clarify opinions and, in some cases, promote a more unified approach. This review aims to discuss the criteria currently in use for the diagnosis of GDM and proposes the universal acceptance of the International Association for Diabetes in Pregnancy Study Group (IADPSG) GDM diagnostic criteria. It also aims to put into perspective the importance of GDM and its increasing prevalence, irrespective of the criteria used for diagnosis. Other factors associated with GDM diagnosis are also covered, including the epidemiology of testing for GDM around the world, the suggested elimination of a two-step diagnostic approach, the cost–effectiveness of testing and the approach to testing in resource-poor settings.